The Effect of Health Promotion Programs on Balanced Nutrition on Changes in Elementary School Children's Eating Patterns - Hilal, Achmad; Nursiah, Andi; Zaenal, Zaenal; Wibowo, Markus (International Journal of Health Sciences, 2025)
Background: Many elementary school children in Indonesia still do not meet balanced nutrition guidelines, as evidenced by low fruit and vegetables consumption and high consumption of fast food. This can impact their nutritional status and long-term health. Objective: To determine the effect of a balanced nutrition health promotion program on changes in elementary school children's eating patterns. Methods: A quasi-experimental study with a pretest-posttest control group design was conducted on 80 fourth-fifth grade elementary school students in Regency X. The sample was divided into an intervention group (n=40) and a control group (n=40). The intervention consisted of health promotion through interactive lectures, posters, and educational games for four weeks. Data were collected using a Food Frequency Questionnaire (FFQ). Data were analyzed using paired t- tests and independent t-tests. Results: There was a significant increase in healthy eating patterns in the intervention group after health promotion (p<0.05), particularly in vegetables and fruit consumption and a decrease in fast food consumption. There was no significant change in the control group (p>0.05). Conclusion: The balanced nutrition health promotion program has been positive impact on the eating habits of elementary school children. It is recommended that schools integrate nutrition promotion into the curriculum and extracurricular activities for sustainability.